Clinical Outcomes and Complications of Preoperative Embolization for Intracranial Giant Meningioma Tumorectomy: A Retrospective, Observational, Matched Cohort Study - Yin, Yi; Li, Yuhong; Jiang, Zhouyang; Zhang, Chao; Ge, Hongfei; Chen, Zhi; Hu, Rong; Chen, Yujie; Li, Xuegang; Li, Fei; Feng, Hua (Frontiers in Oncology, 2022)
Objective: The potential benefits of preoperative embolization for intracranial meningiomas are still under debate. We aim to investigate whether preoperative embolization can improve surgical and functional outcomes, based on controlling patient and tumor related confounding factors. Methods: We reviewed all meningioma cases in our department from January 2016 to May 2021. Cases in the non-embolization cohort were matched to the embolization cohort by 1:1 ratio propensity score matching, through controlling patient and tumor related confounds. Surgical outcomes, complications and functional outcomes were retrospectively compared between these two groups. Results: Sixty-six cases in each group were included in our study after being matched. We didn’t find any significant differences of estimated blood loss (600.00 (400) ml vs. 500.00 (500.00) ml, p = 0.31), decrease of HGB level (30.81 ± 15.82 g/L vs. 26.59 ± 12.90 g/L, p = 0.09), gross total resection rate (74.24% vs. 77.27%, p = 0.68), surgical time (302.50 (136) min vs. 300.00 (72) min, p = 0.48), blood transfusion rates (53.03% vs. 42.42%, p = 0.35), blood transfusion volume (650.00 (657.50) ml vs. 535.00 (875.00) ml, p = 0.63) between the embolization group and non-embolization group. The number of patients experience post-surgery complications were significantly higher in the non-embolization group (39.39% vs. 21.21%, p = 0.02). Patients in the non-embolization group were more likely to have a higher rate of mRS decline post-surgery (31.82% vs. 15.15%, p = 0.04). Conclusion: Our study showed significant lower rates of surgical complications and long-term disabilities of meningioma patients treated with preoperative embolization. There were no significant differences in estimated blood loss, surgical time and blood transfusion volume between embolization and non-embolization groups.